2018
DOI: 10.1186/s11671-018-2494-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity, pH Sensitivity, Noise, and Channel Length Effects in Si Nanowire FET Sensors

Abstract: Silicon nanowire (NW) field-effect transistor (FET) sensors of various lengths were fabricated. Transport properties of Si NW FET sensors were investigated involving noise spectroscopy and current–voltage (I–V) characterization. The static I–V dependencies demonstrate the high quality of fabricated silicon FETs without leakage current. Transport and noise properties of NW FET structures were investigated under different light illumination conditions, as well as in sensor configuration in an aqueous solution wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…The pH-sensitivity of the nanowires can be estimated according to the following expression: 35 with R ch the transistor channel resistance and Δ I DS the modulation of current induced by a change of ΔpH. The sensitivity of the nanowire is 46.4 mV/pH (at zero back gate voltage and V DS =1V) in agreement with the Nernst limit 59.5mV/pH for an ideal surface.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The pH-sensitivity of the nanowires can be estimated according to the following expression: 35 with R ch the transistor channel resistance and Δ I DS the modulation of current induced by a change of ΔpH. The sensitivity of the nanowire is 46.4 mV/pH (at zero back gate voltage and V DS =1V) in agreement with the Nernst limit 59.5mV/pH for an ideal surface.…”
Section: Resultsmentioning
confidence: 62%
“…cm 2 .V − 1 .s − 1 , which is in the range of the bulk values with similar doping concentration, and slightly higher than previously reported value for top-down fabricated nanowires. 30,33,34 The The pH-sensitivity of the nanowires can be estimated according to the following expression: 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the sequencing mechanisms of sensors based on ISFETs can actually be used only for detecting nucleic acid using pH sensitivity and amplifying the useful signal in real time. Static, dynamic characteristics and pH sensitivity of bio FET sensors made on nanosize silicon (nanowire, nanoribbon) are detailed study by us in [15] [16] [17]. In [17] pH sensitivity of the biochemical sensors was introduced as pH ds I ∆ ∆ , where, ds I ∆ and pH ∆ are the elementary changes in source-drain current and pH.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that SNR for Si NW based biochemical sensor has higher value, reaching up to 10 5 . In [15] [16] it is shown that in Si nanosize FET biosensors pH sensitivity increases with the increase of current channel length approaching the Nernst limit value of 59.5 mV/pH, indicating that larger area devices are more suitable for the pH sensing. The pH sensitivity increases also with the increasing of the back-gate voltage and approaches to 59.5 mV/pH.…”
Section: Introductionmentioning
confidence: 99%